Prevention and treatment of bacterial vaginosis in pregnant women with isthmic-cervical insufficiency - Т. Г. Романенко; О. М. Суліменко (Publishing House TRILIST, 2020)
Purpose of the study was to evaluate the effectiveness of clindamycin in combination with metronidazole and miconazole in complex therapy in pregnant women suffering from vaginal dysbiosis with ischemic-cervical insufficiency with threat of premature birth, which used an unloading obstetric pessary. Materials and methods. 100 pregnant women with bacterial vaginosis in the III trimester of pregnancy with isthmic-cervical insufficiency, threat of premature birth and using of an obstetric pessary were examined. 50 women of group I (comparison) received therapy according to the orders of the Ministry of Health of Ukraine, and 50 women of group II (main) used the treatment and preventive measures proposed by study authors, which included Banbact® suppositories for 3 days, and then Gynex® Forte complex drug for 7 days, after which a probiotic of 7 days was prescribed. Results of the study. The clinical effect of treatment in main group was achieved in 100% of cases. The amniotest was negative in all cases after treatment. In both groups was a slight shift to the alkaline side of the vaginal contents (pH 5.0-5.5), in the comparison group 2.5 times more often than in the main one. A significant decrease in the vaginal pH was observed in persons of group II after treatment at 37-38 weeks of pregnancy, no increase in pH >5.5 was detected; pH shift to the alkaline side was observed 3.5 times more often in group I. Most pregnant women in both groups achieved normocenosis after treatment. However, in group I a moderately expressed leukocyte reaction, the prevalence of leukocytes over epithelial cells, and a decrease in normal vaginal flora were noted 2.4 times more often (p <0.05). In 10.0% of pregnant women in group I single spores and pseudo mycelium of fungi, coccal or mixed flora were revealed against the background of a moderate leukocyte reaction (p <0.05). A pronounced leukocyte reaction was retained in 6 (12.0%) women of group II at 37-38 weeks, accompanied by a delay in the fetus development. Mixed flora persisted 3.7 times more often in women of group I. 22 species of microorganisms were identified in group I in the third trimester, while in pregnant women of group II - 14 species. Conclusions. The study revealed the high efficiency of complex treatment for bacterial vaginosis and normalization of the genital tract microflora in the third trimester in pregnant women with isthmic-cervical insufficiency. This helped to reduce the frequency of the threat of abortion, development of placental insufficiency, and delayed fetal development. The clinical efficacy of Banact® and Ginex® Forte was combined with their good tolerance; therefore these drugs are safe during pregnancy, which allows them to be used in practical obstetrics.